Introducing the Tunisia Labor Market Panel Survey 2014 - Ragui Assaad; Samir Ghazouani; Caroline Krafft; Dominique J. Rolando (IZA Journal of Labor & Development, 2016)
This paper introduces the Tunisia Labor Market Panel Survey (TLMPS) of 2014, the first round of a publicly available nationally representative longitudinal household survey. We provide a description of the sample and questionnaires. We discuss a number of data collection issues, such as non-response, as well as what was done to address these issues. The construction of sample weights is detailed. A comparison of the TLMPS to other Tunisian datasets is conducted to illustrate the representativeness of the data in terms of key demographic and labor market measures. Key features of the Tunisian labor market and potential avenues for research using the TLMPS are discussed.
Keywords: J00; C81; C83; 330; Survey data; Public use data; Sample weights; Labor; Tunisia